Anionic or neutral? the charge of Ni8 cubes in metal–organic framework compounds. Issue 67 (29th July 2022) - Freund, Ralph; Kalytta-Mewes, Andreas; Kraft, Maryana; Volkmer, Dirk
Abstract : The cubic SBU Ni8 X6 L6 (X = OH − /H2 O, L = ligand) in MOFs has so far been described as neutral in the literature. We investigated by detailed DRIFTS measurements and exchange reactions whether it shows anionic character, as observed in complexes. Abstract : The cubic SBU Ni8 X6 L6 (X = OH − /H2 O, L = ligand) is of great interest due to its stability and potential applications when integrated in MOFs. Here, we investigate by detailed DRIFTS measurements and exchange reactions whether it is found to be neutral in MOFs, as previously assumed in the literature, or whether it can show anionic character, as observed in complexes.